Incidence and mortality of cervical cancer in Latin America Incidencia y mortalidad de cáncer cervical en América Latina - Silvina Arrossi; Rengaswamy Sankaranarayanan; Donald Maxwell Parkin (Instituto Nacional de Salud Pública, 2003)
Cervical cancer incidence and mortality estimates for 2000 are presented for the 21 Latin American countries, using estimates from the statistical package GLOBOCAN 2000. Additional data on time-trends are also presented, using the WHO mortality database. By the year 2000, some 76 000 cervical cancer and almost 30 000 deaths were estimated for the whole region, which represent 16% and 13% of the world burden, respectively. Thus, Latin American countries are among those with highest incidence rates in the world, together with countries from Sub-Saharan Africa, South and South East Asia. Variation in incidence among countries is large. Very high rates are found in Haiti (ASR 93.9 per 100 000), Nicaragua (ASR 61.1 per 100 000) and Bolivia (ASR 58.1 per 100 000). It seems unlikely that differences in risks in the region can be explained as the result of screening activities. Several descriptive studies carried out to evaluate the screening programmes in Latin America have pointed out problems related to insufficient coverage and frequency of screening. Other related problems include inadequate collection and reading of cytological samplings as well as incomplete follow-up of women after the test. The main challenge for Latin America countries remains on how to organize effective screening programmes, and for this, a real and urgent commitment from public health services and decision-makers in the region is needed. Se presentan estimaciones de la incidencia y de la mortalidad por cáncer cervical para los 21 países latinoamericanos en el año 2000. Se utilizaron el paquete estadístico GLOBOCAN 2000 y las bases de datos de mortalidad de la Organización Mundial de la Salud. En el año 2000, al menos 76 000 casos incidentes de cáncer cervical y 30 000 muertes se estimaron para la Región en general, lo cual representa 16 y 13% del total del mundo, respectivamente. Por lo tanto, los países de América Latina se encuentran en un área geográfica con tasas de incidencia de las más altas en el mundo, junto con países del Sub-Sahara, en Africa, y del sureste de Asia. La variación de la incidencia entre los países es grande; existen tasas muy altas en Haití (93.9 por 100 000), Nicaragua (61.1 por 100 000) y Bolivia (58.1 por 100 000). Es poco probable que las diferencias en los riesgos entre las regiones sean explicadas como resultado de las actividades de tamizaje. Varios estudios descriptivos se han llevado a cabo para evaluar programas de tamizaje en América Latina, señalando problemas relacionados con la frecuencia y la difusión insuficiente del tamizaje. Otro problema relacionado incluye la inadecuada colección y lectura de muestras citológicas, así como el seguimiento incompleto de las mujeres después de la prueba. El principal cambio para los países de América Latina se encuentra en cómo organizar programas efectivos de tamizaje y, para esto, es necesaria una real y urgente integración entre los servicios de salud pública y los tomadores de decisiones en la Región.